The churches' bans on consanguineous marriages, kin-networks and democracy - Jonathan F. Schulz (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
This paper highlights the role of kin-networks for the functioning of modern societies: countries with strong extended families as characterized by a high level of cousin marriages exhibit a weak rule of law and are more likely autocratic. To assess causality, I exploit a quasi-natural experiment. In the early medieval ages the Church started to prohibit kin-marriages. Using the variation in the duration and extent of the Eastern and Western Churches' bans on consanguineous marriages as instrumental variables, reveals highly significant point estimates of the percentage of cousin marriage on an index of democracy. An additional novel instrument, cousin-terms, strengthens this point: the estimates are very similar and do not rest on the European experience alone. Exploiting within country variation of cousin marriages in Italy, as well as within variation of a 'societal marriage pressure' indicator for a larger set of countries support these results. These findings point to a causal effect of marriage patterns on the proper functioning of formal institutions and democracy. The study further suggests that the Churches' marriage rules - by destroying extended kin-groups - led Europe on its special path of institutional and democratic development.
Keywords: O10; N20; N30; Z10; 330; Democracy; Family; Kin-groups; Church; Cousin-Marriage; Institutions